Appraisal of Natural Saltlicks Management of Old Oyo National Park for Wildlife and Eco-Tourism: A Baseline Study (2020)
The use of natural saltlicks (NSs) as valuable hotspots for game viewing and research findings has been embraced by many conservation areas. Currently, there is increased attention of scientists on saltlicks and its utilization, but this has rarely been extended to management strategies for its sustainability. The available studies less focused on guidelines principles for management of NSs, especially in tropical areas like Nigeria. Consequently, there seem to be no regulatory framework specifically meant for the management of such an important niche in Nigeria. This study assesses the effectiveness of management of saltlicks of Old Oyo National Park (OONP). An in-depth interview method of qualitative research was used to harness information from 25 respondents among members of staff purposely selected from among different sectors (ranges) of the study area. The result revealed no specific management guidelines for the protection of NSs of OONP, except for general regulatory laws for the management of wildlife habitat. Many of the park protection staff has little knowledge of the locations of NSs in their respective area, because of incessant transfer of appointment from one range to the other. The study therefore concludes that the impact of threat to NSs at OONP is still at an overwhelming rate but the effectiveness of the management in curbing the disturbance around the NSs is potentially low, especially against the night poachers.